Clinical description of the tissue response on intraoral tattoos (new forms of body art): Pilot study - Pava-Lozano, Juan-Pablo; Valencia-Llano, Carlos-Humberto (Revista Estomatología, 2015)
Objective: Describe the clinical changes observed in the oral mucosa after intraoraltattoos, evaluate tissue reactions for modifications of this type.Materials and methods: It made aa descriptive study of the clinical changes in the oral mucous was made in 11 patients who had had intraoral tattoos were interviewed to obtain general information such as age, socioeconomic status, educational level, presence of extraoral tattoos, body modifications, relevant medical history or problems with their modifications, intraoral tattoos collected data for the design, madedate, color type, location, changes and clinical findings among others. There was a complete stomatological examination, photographs were taken of body modification, intra and extra oral tattoos, it made Photograpic control and monitoring was made at 8, 15, 30 and 60 days before, an data collected in simplified tables.Results: All patients had at least one previous body modification. The most common site of intraoral tattoo was on the lower lip, the design was used with letters, tattoos are preferred monochrome, usually black pigment after 15 days the oral mucous does not seem to irreversible damage at 60 days the tattoo is stabilized, lost some color and definition but apparently does not produce any clinically relevant change.Conclusion: Within the limits of this investigation shows that the material used (pigment black) appears to be biocompatible. Not exist treaty or regulation on the use of specific inks, techniques, types of needle or calibration in the tattoo machines when are making a tattoo in this area, tattoo artists refer to work as best they feel and inks that are reliable on their clinical experiences . Biosafety at the sites of body modifications are becoming more strict and regulated.Key words:Tattoo, intraoral, lip.